Groups of prime power order / volume 3 - Berkovič, Jakov G.; Janko, Zvonimir (Groups of prime power order, 2011)
Biographical note: Yakov Berkovich, University of Haifa, Israel; Zvonimir Janko,Heidelberg University, Germany.